2005
DOI: 10.22358/jafs/67040/2005
|View full text |Cite
|
Sign up to set email alerts
|

Environmental factors and progeny affecting milk yield and composition during the first lactation

Abstract: The purpose of this study was to determine whether the milk yield (MY) of primiparous cows is affected by their housing to weaning, the method of providing liquid feed, sire (S) line, and season of birth and calving. Thirty-two heifer-calves were used in the experiment; 19 heifers were kept in individual housing (IH) and 13 in loose housing (LH) from the second day of life. On the seventh day the IH heifers were divided according to feeding milk replacer (MR) or milk: 10 were relocated from IH to a pen with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Dairy cows calved in the winter and in the spring yielded the most milk, while dairy cows calved in the summer the least (Strabel, 2004;Broucek et al, 2005). Under Mediterranean climatic conditions, summer calvers produce less milk per lactation than winter calvers (Barash et al, 1996).…”
Section: Discussionmentioning
confidence: 96%
“…Dairy cows calved in the winter and in the spring yielded the most milk, while dairy cows calved in the summer the least (Strabel, 2004;Broucek et al, 2005). Under Mediterranean climatic conditions, summer calvers produce less milk per lactation than winter calvers (Barash et al, 1996).…”
Section: Discussionmentioning
confidence: 96%
“…High temperature have not only a direct eff ect on growth of calves, but also a latent eff ect during a dry period of their mothers, especially in the last 60 d of gestation on milk performance of dairy cows (Broucek et al, 2005(Broucek et al, , 2007. Th is may lead to a decreased immunity and transfer of maternal immunoglobulins to colostrum, vigour and ability of the newborn calf to absorb immunoglobulins during hot weather.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, no study assessing for such differences between seasons through the use of non-parametric tests exists. However, Broucek et al (2005) found the same differences in milk yield between seasons using a Kruskal-Wallis test for dairy cattle, reporting the negative effect of summer/autumn months against the positive effect of winter-spring months. The same authors would also agree that fat percentage was statistically higher during summer and autumn months as reported by the results of Dunn's test carried out in our study.…”
Section: Discussionmentioning
confidence: 71%